Rapid Cycle Real-Time PCR: Methods and Applications - Meuer, Stefan (Springer Berlin Heidelberg, 2001)
Rapid Cycle Real-Time PCR allows quantification and sequence analysis in less than 30 minutes. This powerful technique can be applied to any nucleic acid for rapid testing in microbiology, genetics, and oncology. Fluorescence analysis provides convenient determination of product of probe melting temperatures that allows product identification, even down to a single base